2016
DOI: 10.1038/nrcardio.2016.71
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure and sleep disorders

Abstract: Awareness of the importance of sleep-related disorders in patients with cardiovascular diseases is growing. In particular, sleep-disordered breathing, short sleep time, and low sleep quality are frequently reported by patients with heart failure (HF). Sleep-disordered breathing, which includes obstructive sleep apnoea (OSA) and central sleep apnoea (CSA), is common in patients with HF and has been suggested to increase the morbidity and mortality in these patients. Both OSA and CSA are associated with increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(91 citation statements)
references
References 198 publications
2
83
0
6
Order By: Relevance
“…Aging, presence of hypertension, and environmental conditions may modify such physiological response to physical effort, upward shifting, or even steepening the BP–cardiac output relationship 17, 18, 19, 20. This may hold true also for forms of hypoxia‐related BP rise commonly encountered in clinical practice, such as those observed in case of obstructive sleep apnea episodes, which can be characterized by nocturnal hypertension related to hypoxia and sympathetic activation 21. Indeed, we found that exposure to acute hypobaric hypoxia was responsible for both an upward shift and steepening of the BP response to exercise in our middle‐aged, mildly hypertensive individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Aging, presence of hypertension, and environmental conditions may modify such physiological response to physical effort, upward shifting, or even steepening the BP–cardiac output relationship 17, 18, 19, 20. This may hold true also for forms of hypoxia‐related BP rise commonly encountered in clinical practice, such as those observed in case of obstructive sleep apnea episodes, which can be characterized by nocturnal hypertension related to hypoxia and sympathetic activation 21. Indeed, we found that exposure to acute hypobaric hypoxia was responsible for both an upward shift and steepening of the BP response to exercise in our middle‐aged, mildly hypertensive individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Third, disrupted sleep increases sympathetic nervous activity, leading to an increase in blood pressure and heart rate, which demands cardiac activity at a time when the heart should be regenerating 2, 19, 20. In addition, several studies have shown that SA is associated with hypertension, coronary artery disease, arrhythmias, obesity, diabetes mellitus, and metabolic disturbances, all known to increase the risk of HF 2, 3, 21, 22. Hence, we applied many of these comorbidities in our regression models, including continuous assessment of their presence.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep apnea (SA) is associated with increased risk of cardiovascular events, worsening of heart failure (HF), metabolic disturbances, and overall a reduced quality of life 1, 2, 3, 4. One study even found an increased risk of incident HF among men with obstructive sleep apnea (OSA) 5.…”
mentioning
confidence: 99%
“…Inspiratory efforts in OSA against the occluded upper airway are associated with intrathoracic pressure oscillations that result in increased sympathetic activity 4,16) . The hypoxia, hypercapnia, and arousal from sleep that occur at the end of the OSA further increase sympathetic activity.…”
Section: Impact Of Sdb In Hf Patientsmentioning
confidence: 99%